Biodiversity of Sweet Cherry in Sardinia - Luciano De Pau; Ana Fernandes de Oliveira; Alessandra Fabiana Frau; Maria Pia Rigoldi; Riccardo Di Salvo; Giandomenico Scanu; Daniela Satta (Diversity)
The study of biodiversity is of fundamental importance in the context of environmental protection and eco-sustainable agriculture management. Its preservation has a key role and an extraordinary importance not only for the protection of potential gene pools, which is essential for selection and breeding programs, but also because local varieties are the expression of a territory and therefore reflect culture, knowledge, and tradition heritage. In this paper, 27 local cherry varieties collected in different areas of Sardinia were characterized and described from different perspectives, including pomology and genetics, using SSR markers. A complete framework on the biodiversity of cherry trees in Sardinia is presented, in order to support an objective assessment of different cultivar traits, namely those of agronomical interest, and to support the dissemination and conservation of the historical fruit tree cultivation heritage.